Acute and 28-Day Subacute Toxicity Studies of Hexane Extracts of the Roots of Lithospermum erythrorhizon in Sprague-Dawley Rats - Han, Chung-Tack (Toxicol Res, 2015)
Lithospermum erythrorhizon has long been used as a traditional oriental medicine. In this study, the acute and 28-day subacute oral dose toxicity studies of hexane extracts of the roots of L. erythrorhizon (LEH) were performed in Sprague-Dawley rats. In the acute toxicity study, LEH was administered once orally to 5 male and 5 female rats at dose levels of 500, 1,000, and 2,000 mg/kg. Mortality, clinical signs, and body weight changes were monitored for 14 days. Salivation, soft stool, soiled perineal region, compound-colored stool, chromaturia and a decrease in body weight were observed in the extract-treated groups, and no deaths occurred during the study. Therefore, the approximate lethal dose (ALD) of LEH in male and female rats was higher than 2,000 mg/kg. In the subacute toxicity study, LEH was administered orally to male and female rats for 28 days at dose levels of 25, 100, and 400 mg/kg/day. There was no LEH-related toxic effect in the body weight, food consumption, ophthalmology, hematology, clinical chemistry and organ weights. Compound-colored (black) stool, chromaturia and increased protein, ketone bodies, bilirubin and occult blood in urine were observed in the male and female rats treated with the test substance. In addition, the necropsy revealed dark red discoloration of the kidneys, and the histopathological examination showed presence of red brown pigment or increased hyaline droplets in the renal tubules of the renal cortex. However, there were no test substance-related toxic effects in the hematology and clinical chemistry, and no morphological changes were observed in the histopathological examination of the kidneys. Therefore, it was determined that there was no significant toxicity because the changes observed were caused by the intrinsic color of the test substance. These results suggest that the no-observed-adverse-effect Level (NOAEL) of LEH is greater than 400 mg/kg/day in both sexes.